2018
DOI: 10.2147/ijn.s186556
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of the bioreductive prodrug 3-(2-nitrophenyl) propionic acid-paclitaxel nanoparticles (NPPA-PTX NPs) on MDA-MB-231 cells: in vitro and in vivo

Abstract: Background3-(2-Nitrophenyl) propionic acid-paclitaxel (NPPA-PTX) is a paclitaxel (PTX) bioreductive prodrug synthesized by our lab. We hypothesize that NPPA-PTX can self-assemble to form nanoparticles (NPs).Materials and methodsIn the present research, the theoretical partition coefficient (XlogP) and Hansen solubility parameters of NPPA-PTX were calculated. NPPA-PTX nanoparticles prepared by NPPA-PTX and DSPE-PEG (NPPA-PTX:DSPE-PEG =1:0.1, w/w) (NPPA-PTX@PEG NPs) were prepared and characterized. The cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The SRB method was utilized to investigate the cytotoxicity of SNSS NAs in relation to the human pancreatic carcinoma cell lines Panc-1 and BxPC-3. 34 , 42 Briefly, cells were seeded in 96-well plates at a density of 2×10 3 cells/well and incubated for 24 h. The cells were then treated with different concentrations of SNSS NAs, CPT-11, and SN38, respectively. The cells were washed, fixed, and stained with SRB after being exposed to an incubation period of 72 h. Then 10 mM Tris buffer was added, and the OD value of each well was measured at 540 nm using a microplate reader (BioTek Synergy HTX, BioTek Instruments, Inc., Winooski, VT, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The SRB method was utilized to investigate the cytotoxicity of SNSS NAs in relation to the human pancreatic carcinoma cell lines Panc-1 and BxPC-3. 34 , 42 Briefly, cells were seeded in 96-well plates at a density of 2×10 3 cells/well and incubated for 24 h. The cells were then treated with different concentrations of SNSS NAs, CPT-11, and SN38, respectively. The cells were washed, fixed, and stained with SRB after being exposed to an incubation period of 72 h. Then 10 mM Tris buffer was added, and the OD value of each well was measured at 540 nm using a microplate reader (BioTek Synergy HTX, BioTek Instruments, Inc., Winooski, VT, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of NPPA-PTX (Supplementary Scheme 1) and the preparation of NPPA-PTX NPs were reported in our previous work (Song et al, 2016;Duan et al, 2019). NPPA-PTX-FAM was synthesized through click reaction by alkynylation modified NPPA-PTX and 6-FAM-Azid (Supplementary Schemes 2 and 3), and NPPA-PTX-FAM NPs were prepared by the same formulation as the previous research (Duan et al, 2019). Particle size and zeta potential were determined by dynamic light scattering (DLS) measurements (Malvern Zetasizer Nano ZS90, Malvern, UK).…”
Section: Preparation and Characterization Of Nppa-ptx Nanoparticlesmentioning
confidence: 99%
“…The prodrug nanomedicine based on the molecular selfassembly of amphiphilic prodrugs was developed in decades due to their higher loading efficiency and enhanced therapeutic efficiency (Li et al, 2019). In previous research (Song et al, 2016;Duan et al, 2019), PTX was conjugated with 3-(2-nitrophenyl) propionic acid (NPPA) to obtain a novel bioreductive PTX prodrug (NPPA-PTX). The results indicated that NPPA-PTX could completely convert to active PTX in tumor tissues and produce anti-tumor activity.…”
Section: Introductionmentioning
confidence: 99%
“…ALA-PTX NPs were prepared using a simple precipitation method. 16,25,26 In brief, ALA-PTX and DSPE-PEG (ALA-PTX: DSPE-PEG = 1: 0.1, w/w) were dissolved in DMSO. A volume of 1 mL of the above solution was added dropwise into distilled water (3 mL) with stirring (300-500 rpm) at room temperature.…”
Section: Preparation Of Ala-ptx Npsmentioning
confidence: 99%